Effect of different parietal hypoperfusion on neuropsychological characteristics in mild cognitive impairment. Issue 4 (31st May 2021) - Yamaguchi, Tatsuya; Tabuchi, Hajime; Ito, Daisuke; Saito, Naho; Yamagata, Bun; Konishi, Mika; Takebayashi, Minoru; Ikeda, Manabu; Mimura, Masaru
Abstract: Background: In early‐stage amnestic mild cognitive impairment (aMCI), differences in the neuropsychological characteristics of each individual are subtle. We investigated differences in neuropsychological performance between aMCI patients with and without hypoperfusion in the medial parietal regions (MP). We further compared patients with hypoperfusion in the left and right lateral parietal regions. Methods: We examined 165 aMCI patients (mean age: 76.8 ± 5.5 years; 87 women) who had undergone neuropsychological measurement and single‐photon emission computed tomography. We classified participants into two subgroups with and without hypoperfusion: MP hypoperfusion (+) and MP hypoperfusion (−); classification was based on Z‐scores (calculated by three‐dimensional stereotactic surface projection technique) of three regions of interest in the parietal lobes (i.e. MP regions including posterior cingulate cortex and precuneus and left and right inferior parietal lobules (lateral parietal regions)). The MP hypoperfusion (−) group was classified into left lateral parietal hypoperfusion (+) and right lateral parietal hypoperfusion (+) subgroups. We performed either univariate or multivariate ancova to compare neuropsychological scores for continuous variables between groups and examined dichotomous variables using χ 2 tests. Results: In the overall aMCI sample, scores on logical memory delayed recall in the MP hypoperfusion (+) group were significantly lower than those in the MP hypoperfusion (−) group. Total scores on Rey‐Osterrieth Complex Figure Test delayed recall were also marginally lower in the MP hypoperfusion (+) group than in the MP hypoperfusion (−) group. Comparisons of neuropsychological test scores between the left and right lateral parietal hypoperfusion (+) groups revealed no significant differences. Conclusions: The present findings suggest that MP hypoperfusion (+) is associated with more robust memory deficits than MP hypoperfusion (−). Combining neuropsychological tests and single‐photon emission computed tomography findings may be useful for early detection of cognitive decline in aMCI.